Mali : Selected Issues. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2015)
This Selected Issues paper examines growth, structural transformation, and diversification in Mali. At present, the majority of Mali's population is employed in low-productivity agriculture, and the secondary sector is underdeveloped. Further structural transformation and diversification of output and exports could thus yield significant growth dividends, but will be challenging in the context of a rapid projected increase in the workforce over coming decades, much of which would need to be absorbed by the agricultural sector. Policies could focus on easing the constraints to structural transformation in key areas such as education and the business climate, as well as devising a clear strategy for tackling the challenges posed by rapid population growth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet